Foreign language enjoyment in language learning from a positive psychology perspective: a scoping review - Wu, Wenjie; Kabilan, Muhammad Kamarul (Frontiers in Psychology, 2025)
The language learning process is inherently rich in emotional experiences. With the affective turn toward positive emotions in second language acquisition (SLA), foreign language enjoyment (FLE) has gained increasing scholarly attention over the past decade due to its pivotal role in facilitating language learning and improving learners' emotional wellbeing. However, previous studies on FLE have largely adhered to ontological, epistemological, and methodological orthodoxy, often approaching FLE from a static, monolithic, and linear perspective. Moreover, much of this research was conducted without explicitly grounding FLE within the framework of positive psychology (PP). In response to these issues, this scoping review aims to provide an innovative examination of FLE through the lens of PP and to provide novel insights into its role in SLA. By evaluating 36 studies on FLE within the framework of PP, this article highlights the dynamic, interactive, and context-sensitive nature of emotions. It synthesizes key research themes and contextual and methodological characteristics while identifying current research gaps. Finally, this review presents implications and provides recommendations for future relevant research in this area.